2022
DOI: 10.1177/03331024221123081
|View full text |Cite
|
Sign up to set email alerts
|

Perceived barriers to career progression in the headache field: A global web-based cross-sectional survey

Abstract: Background It is well recognized that underrepresented and minoritized groups do not have the same career opportunities. However, there are limited data on the range and specifics of potential barriers that withhold people in headache medicine and science from reaching their full potential. Moreover, people from different geographical regions often perceive different challenges. We aimed to identify world-wide perceived career barriers and possibilities for promoting equality amongst professionals in the heada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The majority of participants were in a relationship (82.7%; 479/579), and had children (71.8%; 416/579). Additional respondents’ characteristics can be found in Table 1 (24). Almost half of respondents indicated that they had experienced harrasment in the workplace (46.6%; 270/579).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of participants were in a relationship (82.7%; 479/579), and had children (71.8%; 416/579). Additional respondents’ characteristics can be found in Table 1 (24). Almost half of respondents indicated that they had experienced harrasment in the workplace (46.6%; 270/579).…”
Section: Resultsmentioning
confidence: 99%
“…Using a non-experimental cross-sectional exploratory survey approach with a quantitative design, we conducted a global-wide survey aimed at headache professionals, including medical doctors, other healthcare providers and all those that are involved in the field of headache research. This study was part of a previously published effort to determine relevant career barriers for headache professionals (24). In short, (associate) members of the International Headache Society (IHS), and delegates of the 2019 International Headache Congress (IHC) were sent the web-based survey by email.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even the industries with a higher presence of women are not an exception to the progression of women career. For instance, de Boer et al, (2022) outlines that in academia women not only publish few articles as first authors but these articles have fewer citations (Chatterjee & Werner, 2021;Filardo et al, 2016). Research also reveals that women receive less funding for their proposed study where gender is deemed partially responsible for decisions relating to awarding of grants.…”
Section: Career Progressionmentioning
confidence: 99%
“…Additionally, past research on Pygmalion Effect is conducted on industries such as banks (Khan et al, 2022), pharmaceutical, chemical, engineering and manufacturing (Farrukh et al, 2022). Furthermore, extensive research has been conducted on career progressions in the fields of healthcare (de Boer et al, 2022), veterinary surgeons (Treanor & Marlow, 2021), and government agencies (D'Agostino & Levine, 2010). Evidently, the real estate sector has rarely been considered to explore Pygmalion Effect and female career progression.…”
Section: Introductionmentioning
confidence: 99%